Hipotermia na resposta inflamatória após sessão de exercícios resistidos em adultos destreinados - Missau, Edson (2017)
Resisted exercises are especially used to increase hypertrophy and muscle strength in healthy individuals or rehabilitation. In all cases, exercises performed at high intensity may promote oxidative stress, which triggers an inflammatory process resulting in delayed onset muscle soreness (DOMS). DOMS decreased functionality and the consequent abandonment of regular exercise practice, especially in untrained individuals. Different non-pharmacological techniques are used to reduce DOMS and to attenuate its consequences, among which are the antioxidant supplementation (vitamins C and E) and cold water immersion baths. This present research aims to verify the interventions in hematological dynamics, inflammatory markers and oxidative stress of healthy untrained volunteers submitted to hypothermia by immersion in cold water after a session of resistance exercises. Methods: Thirteen volunteers (26 ± 5 years old) non-RE practitioners were randomized and submitted to sessions ER Control and ER with CWI. Exercises sessions (extensor chair, squat and leg press) consisted of four sets of 10 maximum repetitions (one week interval between the evaluation and the sessions). CWI consisted of immersion in water (15°C) at the umbilical scar level for 10 minutes immediately after the exercise session. Complete blood count, high-sensitivity CRP, creatine kinase (CK) and lipoperoxidation (LPO) were previously assessed (baseline), immediately, 30 minutes and 120 minutes after RE. DOMS was evaluated 24 hours after the sessions. Results: RE induced a progressive leukocytosis (P<0.001). CRP was elevated 120 minutes after the exercises (P=0.008) only in the RE Control session. CK increased after 30 minutes and 120 minutes after exercise (P<0.001) in the Control session, whereas in the CWI session the increase was observed after 120 minutes (P<0.001). LPO increased only in the Control session in 120 minutes (P=0.025). CWI reduced the DOMS by 57% (P<0,001). Conclusion: CWI slows the inflammatory response and reduces DONS in untreated individuals submitted RE.